EFFECT OF BORASSUS ACTHIOPUM EXTRACT AS A BIOLOGICAL EXTENDER ON SEMEN CHARACTERISTICS, FERTILITY AND HATCHABILITY IN CHICKEN - Adebisi, Adeyina Oluwatoba; Akanbi, Ademola Samuel; Okukpe, Kehinde Matthias; Ogbah, Odemairo Issac; Adegboye, Adiru Afolabi; Moshood, Moshood Afolabi (Journal of Agricultural Sciences (Belgrade), 2017)
Abstract: Borassus aethiopum extract as a biological extender was evaluated on semen quality, fertility and hatchability and chicken under warm preservation of 37 degree centigrade. The extenders were and 1: 5 and 1:10 (extract to normal saline) and preserved for 0, 1, 2, 3 and 4 hours respectively and a factorial design layout. There was no significant (p> 0.05) Effect of extender on semen characteristics within 2 hours of preservation. However, motility (%) significantly (p